Reappraisals and new studies of the modern Jewish experience : essays in honor of Robert M. Seltzer - Smollett, Brian M. (The Brill Reference Library of Judaism, 2015)
Reappraisals and New Studies of the Modern Jewish Experience brings together twenty scholars of Modern Jewish history and thought. The essays provide a fresh perspective on several central questions in Jewish intellectual, social, and religious history from the eighteenth century to the present in the contexts of Russia, Western and Central Europe, and the Americas.